Goal-setting and reputation enhancement: behavioural choices among delinquent, at-risk and not at-risk adolescents - Carroll, Annemaree (Legal and criminological psychology, 2001)
Purpose. The purpose of the present research was to investigate the relationships among goal-setting, reputation enhancement (striving to project a nonconforming, tough image) and delinquent behaviour in adolescents. Methods. Participants were 80 incarcerated delinquent, 90 at-risk and 90 not at-risk adolescent males, ranging in age from 12 to 18 years, who completed four scales: the Adapted Self-Report Delinquency Scale, the Importance of Goals Scale, the Reputation Enhancement Scale, and the Rosenberg Self-Esteem Scale. Results. Four second-order factors (self-reported delinquency, self-presentation, conforming reputation, non-conforming reputation) were derived from the 31 first-order factors of the four scales. A series of multivariate analyses of variance (MANOVAs) and univariate F tests were then performed on each of the four sets of dependent variables which revealed that the goals of delinquent and at-risk participants were more congruent with a non-conforming reputation, compared to those of the not at-risk participants who set goals which were more congruent with a conforming reputation. Conclusions. The integration of goal-setting theory and reputation enhancement theory tested in this research provides an alternative analysis of delinquency using a social-psychological approach. Identification of the phenomenon of nonconforming reputation enhancement among delinquent and at-risk adolescents highlights the necessity to provide a differentiated intervention for working with these particular young people.